PSYCHOLOGICAL STRATEGIES FOR BUILDING QUALITY HUMAN RESOURCES IN MADRASAH - Aini, Tsamar Nur; Baharun, Hasan; Hamid Wahid, Abd.; Manshur, Umar; Mundiri, Akmal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Human resource management in the educational environment, especially in secondary schools, is the main focus in ensuring the implementation of an optimal learning process. The main aim of this research is to provide a comprehensive understanding of all human resources in an effort to improve quality HR management. This research is qualitative research which aims to understand psychological strategies for building quality human resources (HR) at (MAN) 1 Probolinggo. This research is qualitative research which aims to understand psychological strategies for building quality human resources (HR) at (MAN) 1 Probolinggo. This research method uses a qualitative approach with three main data collection techniques: participant observation, semi-structural interviews, and document analysis. The results of the research show that the psychological strategies implemented will produce students who have positive character, are able to manage stress and learning pressure, have strong social skills, and can develop holistically. By implementing psychological strategies, MAN 1 Probolinggo is committed to creating an environment education that supports students' integral growth and forms quality human resources.